Т. 5; Измерения и испытания; Вибрации в технике - Алесенко В. В. Владимир Владимирович; Больших А. С. Артемий Степанович; Генкин М. Д. Михаил Дмитриевич; Гик Л. Д.; Генкин М. Д. (1981, 1981)
Авт. указ. на обороте тит. л.